Evaluation of Microincision Vitrectomy Surgery Using Wide-Viewing System for Complications With Ocular Sarcoidosis. Issue 7 (February 2015) - Takayama, Kei; Tanaka, Atsushi; Shibata, Masanori; Muraoka, Tadashi; Ishikawa, Sho; Harimoto, Kouzo; Takeuchi, Masaru
Abstract : Abstract: We evaluate the outcomes of microincision vitrectomy surgery (MIVS) using wide-viewing system for complications with ocular sarcoidosis resistance to medical treatment. Consecutive clinical records of 24 eyes (19 patients) with complications of ocular sarcoidosis underwent MIVS between April 2010 and December 2013 were retrospectively reviewed. MIVS and phacoemulsification were performed in 18 eyes and MIVS only in 6 eyes. Best-corrected visual acuity (BCVA), inflammation scores in the anterior segment and in the posterior segment, and central retinal thickness (CRT) of eyes with cystoid macular edema (CME) before surgery and after 1 week, 1, 3, 6, and 12 months were evaluated. LogMAR (log of the minimum angle of resolution) converted from BCVA was improved in 83.3% after 12 months and 66.7% showed improvement of more than 2 lines. The mean LogMAR was significantly improved from 1.14 ± 1.18 to 0.36 ± 0.79 in all eyes and 0.83 ± 0.86 to 0.23 ± 0.41 in eyes with MIVS and phacoemulsification, although no improvement was observed in eyes with MIVS only. Significant decrease of the mean anterior inflammation score was observed after 1 month in eyes with MIVS only and after 12 months in eyes with MIVS and phacoemulsification, and the mean posterior inflammation scores decreased after 1 week in all eyes. In eyes with preoperative CME, mean CRT was significantly decreased from 1 week after surgery. There was no case in which ocular inflammation was exacerbated by surgical stress. Improvement of visual acuity and resolution of ocular inflammation could be achieved by MIVS using wide-viewing system for complications of ocular sarcoidosis.